Dopant‐Free Hole‐Transporting Layer Based on Isomer‐Pure Tetra‐Butyl‐Substituted Zinc(II) Phthalocyanine for Planar Perovskite Solar Cells. Issue 9 (2nd September 2019) - Dong, Lei; Hu, Qikun; Rezaee, Ehsan; Chen, Qian; Yang, Songhe; Cai, Siyuan; Liu, Bingchen; Pan, Jia-Hong; Xu, Zong-Xiang
Abstract : In article no.1900119, Zong‐Xiang Xu and co‐workers synthesize isomer‐pure 2, 9, 16, 24‐tetra‐n‐butyl‐Zn (II) phthalocyanine ( RE ‐ZnBu4 Pc) through ring expanding of symmetric tri‐n‐butyl‐substituted boron subphthalocyanine as a dopant‐free hole transporting material (HTM) in planar conventional perovskite solar cells, which offers higher efficiency, long‐term stability, and reproducibility than HTMs based on ZnBu4 Pc with an isomer mixture.